2014
DOI: 10.1038/nutd.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior traits and sleep as determinants of weight loss in overweight and obese adults

Abstract: Objective:To examine the associations between eating behavior traits and weight loss according to sleep quality and duration in adults enrolled in common weight-loss interventions.Methods:Participants included overweight and obese men and women (n=150) (mean±s.d. age, 38.8±8.6 years; mean±s.d. body mass index (BMI), 33.3±3.5 kg m−2) who were subjected to a dietary intervention over a period of 12–16 weeks. Anthropometric measurements, eating behavior traits (Three-Factor Eating Questionnaire), sleep quality (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…The Pittsburgh Sleep Quality Index measures 7 domains including subjective sleep quality, sleep onset latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleep medication, and daytime dysfunction over the last month to distinguish between poor and good sleepers. A global sum ≥5 indicates poor sleep 24, 25, 26. According to the Sleep Research Society/American Academy of Sleep Medicine consensus statement,27 adequate sleep should be ≥7 hours/night, while sleeping <7 hours/night is considered insufficient.…”
Section: Methodsmentioning
confidence: 99%
“…The Pittsburgh Sleep Quality Index measures 7 domains including subjective sleep quality, sleep onset latency, sleep duration, habitual sleep efficiency, sleep disturbances, use of sleep medication, and daytime dysfunction over the last month to distinguish between poor and good sleepers. A global sum ≥5 indicates poor sleep 24, 25, 26. According to the Sleep Research Society/American Academy of Sleep Medicine consensus statement,27 adequate sleep should be ≥7 hours/night, while sleeping <7 hours/night is considered insufficient.…”
Section: Methodsmentioning
confidence: 99%
“…During 17 weeks of moderate caloric restriction among 123 overweight and obese adults, sleep duration and sleep quality at baseline predicted fat loss . Also among 150 obese (BMI 33.3 ± 3.5 kg/m 2 ) men and women (age 38.8 ± 8.6 years), sleep quality (assessed by Pittsburgh Sleep Quality Index) was associated with loss of body weight, fat mass and waist circumference . Furthermore, better subjective sleep quality among 245 women enrolled in a 6‐month weight‐loss programme increased the likelihood of successful weight loss by 33% .…”
Section: The Influence Of Stress On Sleep Patterns and Quality: Linksmentioning
confidence: 97%
“…Standardized laboratory studies in humans have confirmed the validity of this relationship that is likely explained by numerous effects promoting a positive energy balance. These effects include an increase in the orexigenic hormones ghrelin and cortisol , a decrease or a lower than predicted plasma concentration of the anorexigenic hormone leptin , an accentuation of mild hypoglycaemia that is predictive of long‐term weight gain , an increase in ad libitum energy intake , a decrease in physical activity , an increase in alcohol consumption and suboptimal eating behaviours .…”
Section: The Need To Better Understandmentioning
confidence: 99%